Study of a flat-surface, high-pressure, pool boiling test instrument - Wenhua Yu; David M. France; Meltem Urgun-Demirtas; Dileep Singh (Case Studies in Thermal Engineering, 2023)
A study has been conducted of a newly developed high-pressure instrument, capable of pool boiling testing on multiple flat surfaces without instrumentation of each sample tested. The instrument has a unique design for testing flat samples with instrumentation only in the instrument and a data reduction procedure appropriate for the design. The validity of the instrument design and data reduction procedure was verified through boiling water heat transfer testing on a flat stainless-steel surface at atmospheric and 0.69-MPa pressures. The boiling heat transfer results obtained were shown to be in reasonable agreement with predicted values from correlations in the engineering literature. This test instrument is especially useful for evaluating the performance of newly engineered surfaces, such as textured and coated surfaces, compared to that of the base surface, where experimental testing on the base and engineered surfaces under the same operation conditions is required, and instrumentation of the surfaces would be detrimental to them.